ANALISIS KEBANGKRUTAN BANK - Sri Haryati (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
Due diligence evaluation by a special committee to commercial banks has classified the banks into three ratings: Rated a for banks with a minimum capital adequacy ratio (CAR) of 4%, rated B for those with CAR between –25% and 4%, and rated C for those with CAR less than –25%. CAR is one of the criteria to assess the financial health of commercial banks. Other aspects of evaluations are capital asset quality, management, earnings, and liquidity (CAMEL). These aspects are interrelated and it is important to evaluate the impact of each aspect on the probability of commercial bank bankruptcy. This study attempts to test whether several important ratios determine the probability of bankruptcy for all classes of commercial banks. ANOVA is used to test whether the categories of banks are statistically different in terms of those ratios. Logistic regression model is also applied to predict the probability of bank bankruptcy. The empirical results show that efficiency and LDR ratios are statistically different for the three categories. Furthermore, those ratios are statistically significant to predict the probability of bankruptcy at 0.05 level of significance with the correct classification of 75.5%. The results imply that bank management should maintain the financial heath of the bank by all measures to improve the ratios when they fall in the lower limit of the criteria.